PENGARUH KEPADATAN BATERAI TERHADAP PRODUKTIVITAS AYAM PETELUR DALAM KANDANG CLOSED HOUSE - Sasvia Candra, Dewi; Ari kustanti, Nita Opi (AVES: Jurnal Ilmu Peternakan, 2023)
This study set out to ascertain how variations in battery density affected the body weight and egg weight of layer phase laying hens housed in closed house cages. The study ran from November 2022 through January 2023. Twelve batteries, or 180 hens, were employed in each sample for each variable. The battery that is being utilized measures 60 by 65 cm. Egg weight and body weight are the factors used. Purposive sampling is the approach utilized for data collecting; an experimental T test is used to identify differences, and a correlation test determines the strength of the association. The study's significance value is (p˃0,05), indicating that there is no significant difference in the body weight and egg weight of the eight hens in the battery compared to the density of the battery with seven chickens. It is nevertheless possible to house chickens in cages of varying densities because there is a weak link between body weight and egg weight.